Institute of State Secrets: the Post-Soviet Space - Raphael Midkhatovich Yusupov; Mikhail Aleksandrovich Vus (Управленческое консультирование)
The article is devoted to separate aspects of formation and development of legislative regulation of the Institute of state secrets (state secrets) in the post-Soviet States. Focuses on the difference between the legal concepts of “state secret” and “state secrets.” Stresses the urgency of improving the legal security, convergence and harmonization of legislation on state secrets to the member States of the organization of collective security Treaty. Discusses the approach to developing the Model law.